The encyclopedia of money - Allen, Larry 1949-; Gale Group (Santa Barbara, California ABC-CLIO, 2009)
Covers the development of money and the functions and dysfunctions of the monetary and financial system.
Electronic reproduction.
Keywords: Money -- Encyclopedias; Monetary policy -- Encyclopedias; Electronic books